Cell type-dependent uptake, localization, and cytotoxicity of 1.9 nm gold nanoparticles - Coulter JA (Dove Medical Press, 2012)
Jonathan A Coulter,1 Suneil Jain,2 Karl T Butterworth,2 Laura Taggart,2 Glenn Dickson,2 Stephen J McMahon,3 Wendy Hyland,1 Mark F Muir,3 Coleman Trainor,2 Alan Hounsell,2,4 Joe M O'Sullivan,2,4 Giuseppe Schettino,2 Fred Currell,3 David G Hirst,1 Kevin M Prise21School of Pharmacy, McClay Research Centre, 2Centre for Cancer Research and Cell Biology, 3School of Mathematics and Physics, Queens University Belfast, 4Belfast Health and Social Care Trust, Belfast, IrelandBackground: This follow-up study aims to determine the physical parameters which govern the differential radiosensitization capacity of two tumor cell lines and one immortalized normal cell line to 1.9 nm gold nanoparticles. In addition to comparing the uptake potential, localization, and cytotoxicity of 1.9 nm gold nanoparticles, the current study also draws on comparisons between nanoparticle size and total nanoparticle uptake based on previously published data.Methods: We quantified gold nanoparticle uptake using atomic emission spectroscopy and imaged intracellular localization by transmission electron microscopy. Cell growth delay and clonogenic assays were used to determine cytotoxicity and radiosensitization potential, respectively. Mechanistic data were obtained by Western blot, flow cytometry, and assays for reactive oxygen species.Results: Gold nanoparticle uptake was preferentially observed in tumor cells, resulting in an increased expression of cleaved caspase proteins and an accumulation of cells in sub G1 phase. Despite this, gold nanoparticle cytotoxicity remained low, with immortalized normal cells exhibiting an LD50 concentration approximately 14 times higher than tumor cells. The surviving fraction for gold nanoparticle-treated cells at 3 Gy compared with that of untreated control cells indicated a strong dependence on cell type in respect to radiosensitization potential.Conclusion: Gold nanoparticles were most avidly endocytosed and localized within cytoplasmic vesicles during the first 6 hours of exposure. The lack of significant cytotoxicity in the absence of radiation, and the generation of gold nanoparticle-induced reactive oxygen species provide a potential mechanism for previously reported radiosensitization at megavoltage energies.Keywords: endocytosis, proliferation, reactive oxygen species, transmission electron microscopy